The Revitalization of Tari Buku Nias Utara as a Teaching Material of Appreciation for Nias Dance Techniques Subject - Tuti Rahayu; Sitti Rahmah; Iskandar Muda (BIRCU, 2020)
The purpose of this research is to revitalize Tari Buku from Nias Utara area which is almost extinct and to re-present it as a performance and its development in the Muslim community in Lahewa Nias Utara. From this revitalization process emerged the development results in the form of history, functions, make-up and clothing for Tari Buku and the local culture of Nias Utara. The method used is the R&D methodology. The location of this research was conducted in Lahewa sub-district, North Nias district. Data collection techniques through observation, in-depth interviews and documentation. The data that has been collected, and then analyzed using a qualitative paradigm with a project based research method, which is obtained through data reduction, data testing and drawing conclusions. The data validity test used the source triangulation model and the triangulation technique. The results of the development are used in learning the Nias dance technique subject to Dance Education students at Universitas Negeri Medan.